Duodenal pH : new aspects of physiology and pathophysiology - Eriksen, Craig Alexander (Department of Surgery, 2018)
The pathogenesis of duodenal ulcer is believed to centre around the presence of gastric acid, yet the exact role that acid plays is poorly understood. Previous investigations of the duodenal pH have been restricted by methodological and technical difficulties, and have, for the most part, only monitored the pH in the short-term. A new reliable system for long-term (twenty-four hour), ambulatory, simultaneous measurement of intra-luminal antral and duodenal bulb pH has been developed. The system comprises two glass pH electrodes, a small portable recording unit and a computer-based system for data storage and analyses. Validation of this pH monitoring system was first performed, and the 24-hour ambulatory profiles of antral and duodenal pH of normal healthy subjects were subsequently recorded. Periods of cephalic stimulation and ingestion of a solid meal were included during the study period. Having established the normal profiles, the investigation was repeated in patients with active duodenal ulcer, off-treatment. The gastric pH profile was similar of both study groups. There were no significant differences between the fasting duodenal bulb pH and the total 24-hour duodenal acid exposure of the ulcer patients and healthy subjects. Acid peak analysis demonstrated that the duodenal ulcer patients exhibited a defect in the propulsive duodenal bulb motility. Gastric stimulation caused a similar pattern of duodenal acidification in the two groups. These results suggest that gastric acid is not of primary pathophysiological importance in duodenal ulcer disease. The effects of cephalic stimulation and a meal on plasma gastrin, secretin and somatostatin and duodenal pH were examined in healthy subjects and duodenal ulcer patients. The results showed: vagally-released gastrin is not a significant contributor to stimulation of gastric acid secretion in either health or duodenal ulcer disease; duodenal ulcer patients have excessive basal and post-stimulation plasma gastrin levels but a subset of ulcer patients exists, the "Hypergastrinaemic" patients, who exhibit exaggerated gastrin responses, vagal hyperactivity, a defective somatostatin-induced inhibition of gastrin release and a defect in the "switch-off" mechanism of gastric acid secretion. In addition, the physiological role of secretin in inhibiting gastrin release in Man is questionable. This study reveals new aspects in the physiology and pathophysiology of the duodenal bulb pH.